2018
DOI: 10.21608/taec.2018.11916
|View full text |Cite
|
Sign up to set email alerts
|

Pollen and Seed Morphology of Some Endemic Taxa in Saint Catherine, Sinai, Egypt

Abstract: Macro-and micro-morphological features of seeds and pollen grains of 12 endemic taxa belonging to seven families collected from Saint Catherine area, South Sinai, Egypt were examined by light microscope (LM) and scanning electron microscope (SEM). Macro-and micro-morphological characters, of seeds including shape, colour, size, brightness, seed surface, epidermal cell shape, anticlinal boundaries, and periclinal cell wall are presented. Pollen description includes shape, size, apertures and exine ornamentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…All pollen grains are isopolar, except Buffonia multiceps, S. leucophylla, S. oreosinaica, S. schimperiana (belonging to Caryophyllaceae) which are a polar. Such result is in accordance with Rabei et al (2016) and other previous studies on this family (Yildiz 2005), but disagrees with El-Ghamery et al (2018) since they reported that all endemic taxa in their study are isopolar. The shape class of the examined pollen grains is subprolate in S. oreosinaica and Origanum syriacum subsp.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…All pollen grains are isopolar, except Buffonia multiceps, S. leucophylla, S. oreosinaica, S. schimperiana (belonging to Caryophyllaceae) which are a polar. Such result is in accordance with Rabei et al (2016) and other previous studies on this family (Yildiz 2005), but disagrees with El-Ghamery et al (2018) since they reported that all endemic taxa in their study are isopolar. The shape class of the examined pollen grains is subprolate in S. oreosinaica and Origanum syriacum subsp.…”
Section: Discussionsupporting
confidence: 85%
“…Four taxa belonging to Caryophyllaceae are characterized by the presence of annulus which is absent in the rest of the studied taxa. These findings corroborate with Yildiz (2005); Krachai et al (2009); Pinar et al (2009); Osman (2012); Mostafavi and Mehregan (2014);El-Ghamery et al (2018) and Shiha (2020).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The pseudo-fruits (rosehip) of R. canina ( figure 1 ), often referred to as ‘fruits’ in literature sources, are aggregate fruits consisting of several achenes (the actual one seed-containing fruits of dog rose) enclosed by an enlarged fleshy floral cup (hypanthium) [ 28 ]. The rosehip has been analysed at macro- and micro-scale through achene morphology [ 29 , 30 ], morpho-anatomical characterization of achenes, mainly pericarp [ 31 , 32 , 33 ] and seed morphology [ 34 ]. In the upper part of the hypanthium, there is a small opening, filled with protruding styles ( figure 1 b ).…”
Section: Resultsmentioning
confidence: 99%